2006
DOI: 10.1007/s00210-006-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils-derived peroxynitrite contributes to acute hyperalgesia and cell influx in zymosan arthritis

Abstract: We investigated the contribution of neutrophils to joint hyperalgesia and peroxynitrite formation in zymosan arthritis. Rats received 1 mg zymosan intra-articular, and joint hyperalgesia was measured using the rat knee-joint articular incapacitation test. After 6 h, joint exudates were collected by aspiration for the assessment of cell influx, myeloperoxidase activity, and nitrite (as an index of nitric oxide formation) levels. Nitrotyrosine content, used as an index of peroxynitrite formation, was measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 40 publications
2
27
0
4
Order By: Relevance
“…In the knee joint, zymosan is able to simulate an inflammatory response like that observed in the arthritis development, in which both resident synovial and infiltrated immune cells produce several mediators of inflammation, including nitrogen and oxygen-derived free radicals, cytokines, leukotrienes, and prostaglandins, which have been associated with the degradation of articular cartilage (4,46,47). Frasnelli et al (19) demonstrated that Toll-like receptor (TLR) 2 is the major pathway of proinflammatory signaling in zymosan-induced arthritis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the knee joint, zymosan is able to simulate an inflammatory response like that observed in the arthritis development, in which both resident synovial and infiltrated immune cells produce several mediators of inflammation, including nitrogen and oxygen-derived free radicals, cytokines, leukotrienes, and prostaglandins, which have been associated with the degradation of articular cartilage (4,46,47). Frasnelli et al (19) demonstrated that Toll-like receptor (TLR) 2 is the major pathway of proinflammatory signaling in zymosan-induced arthritis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…While NO per se appears to be beneficial to joint homeostasis (5,10,11), the combination of NO with other reactive species, such as the superoxide anion, may result in peroxynitrite formation and subsequent tissue lesion (23). We have recently demonstrated that neutrophils contribute to the formation of peroxynitrite in ZYA (4). Hence, the reduced formation of reactive oxygen species secondary to the reduced neutrophil cell influx may participate in the benefit provided by the A. suum extract in arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, the redox environment surrounding the cells changes due to rapid production of reactive oxygen species. Increased levels of reactive oxygen species are implicated in the etiology of inflammatory hyperalgesia (14,(21)(22)(23)(24). Importantly, TRPV1 was found to be responsible for long sustained thermal hypersensitivity in inflammatory hyperalgesia induced by increased levels of hydrogen peroxide (H 2 O 2 ) (25).…”
mentioning
confidence: 99%